All-Polyethylene Tibial Component Does Not Affect Survivorship of Medial Unicompartmental Knee Arthroplasty at Mid-Term Follow-Up - Gagliardi, Michele; Zambianchi, Francesco; Franz, Alois; Digennaro, Vitantonio; Catani, Fabio (The Journal of Knee Surgery, 2020)
The present study's primary aim was to determine the survivorship of a large cohort of patients implanted with a single design all-polyethylene tibial component medial unicompartmental knee arthroplasty (UKA). Its secondary purpose was to investigate the reasons underlying implant failure, with specific attention to component positioning and limb alignment. Between 2007 and 2013, 166 patients underwent medial UKA with a single design all-polyethylene tibial component at two centers. Preoperatively and postoperatively, patients were administered clinical outcome scores and radiographic information were collected. Postoperative complications and causes of revision were recorded. A total of 140 patients (80 in Center A and 60 in Center B) who underwent all-polyethylene tibial component medial UKA (82 cases in Center A and 60 in Center B) were taken into account. Kaplan–Meier cumulative survivorship of implants was 96.5% (confidence interval [CI]: 91.7–98.6%) at an average follow-up of 61.1 months. Tibial aseptic loosening was accounted for failure in one case, while no correlation was found between implant positioning and failure. Two revisions were performed in Center A and three in Center B. Slight correction of the preoperative varus deformity was performed at both centers. All-polyethylene tibial component UKA provided satisfactory clinical and functional outcome, with excellent survival rate in the early and mid-term follow-up. Continued patient follow-up is needed to determine long-term survivorship of the examined UKA model.
Keywords: all-polyethylene; unicompartmental knee arthroplasty; survivorship; alignment